Interferência da rugosidade hidráulica gerada pela vegetação emersa no transporte de sedimentos no Rio Capibaribe - SILVA, Yuri Jacques Agra Bezerra (2012)
The vegetation plays an important role on sediment transport processes, being essential to improve the knowledge regarding the unsubmerged vegetation interference in this process. Thus, the main aim of this research was to assess the hydraulic roughness interference generated by unsubmerged vegetation on sediment transport, based on relationship between vegetation drag coefficient (CD’) and Reynolds number of vegetation (Replant) from Capibaribe River. Direct measurements campaigns were carried out according to the equal-width-increment (EWI), using the US DH-48 sampler to suspended sediment sampling and US BLH 84 sampler to bedload sampling. It was evaluated the resistance generated by Echinodorus macrophyllus by means of the vegetation drag coefficient (CD’) and vegetation drag force (FD) as well as the influence of these parameters on sediment transport of Capibaribe watershed. Furthermore, principal component analysis (PCA) and hierarchical cluster analysis (HCA) were performed to choose the most important variables associated with the sediment transport and classify the thirteen direct measurement campaigns in groups according to the similarity, respectively. The CD’ reached a maximum value equal to 11.13 m-1, indicating the hydraulic resistance generated by Echinodorus macrophyllus. The first two components extracted had eigenvalues equal to 6.74 and 3.15, accounting for the 90.03% of the total variance explained. The HCA revealed five clusters in which the second was formed by the direct measurement campaigns carried out with unsubmerged vegetation along the cross section (C2, C4 and C6). These measurements showed the lowest values, chiefly to the shear stress and bedload discharge. The last cluster was formed by the direct campaigns (C10, C11, C12 and C13) which mainly gathered the largest values of hydraulic radius, water discharge, bedload discharge and shear stress. As a result, the multivariate analysis was considered an adequate tool for evaluating the interference of unsubmerged vegetation on sediment transport of Capibaribe watershed.